Transformative Impact: The Evolution of Learning through AI in Education - Viviana Lisma Lestari (Penelitian dan Pengembangan Ilmu, 2024)
Education has become a field increasingly integrated with artificial intelligence (AI), opening the door to innovation in learning and teaching processes. In this study, we conducted a systematic review of the existing literature to describe the basic concepts of AI in education and their implications. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method was used to organize the process of literature search, selection and analysis. The results of our review show that the use of AI in education has great potential to improve learning personalization, administrative efficiency, and teaching effectiveness. The implications of these findings highlight the need for a careful approach in integrating AI in educational curricula, as well as the importance of training educators in AI literacy.